دور المدرب في الانتقاء الرياضي المبني على الأسس العلمية لدى الناشئين لكرة القدم صنف (9-12)سنة - شنوف, خالد (My University, 2018)
The process of preparation of elite athletes to participate in sports competitions is very important which focus on several factors; the most important factor is selecting players by scientific basics. Where there is no fixed criteria based on scientific to select athletes where They depend on observation and bring the children to participate in sports competitions. In this study, we tried to identify the importance and the role of the trainer in sports selection that based on scientific basics to young footballers class (9-12Year). Where in the beginning, we wanted to know the role of the sports coach in the training process, which have a positive impact in the preparation of the players, because the sports selection based on scientific basics which is very important To reach players to the highest level allowed by their abilities and readiness. In order to ensure the best results it must be on the trainers selection to use all scientific methods and applied knowledge in the selection for the desired results. Moreover, through what we have done in this research from the theoretical study and the field study we have find that the coach has an effective role in the selection process based on scientific basics, as well as the experience of the coach have a positive impact on the selection process. Where whenever the trainer has experience and high efficiency could control the selection process. Thus raising the level in the Algerian Football Clubs. The researcher extract several recommendations, including the scientific methods in the selection process-.Programming of Special Scheme selection process in terms of the steps of the methodology and the use of the measurements and tests in order to control this process in terms of time and how - Keywords: Coach -selection sports - Football.
Keywords: المدرب الرياضي -الانتقاء الرياضي -كرة القدم.